Analysis of Personal Hygiene and Characteristics of Living Environment in Elementary Student with Pediculosis Capitis - Petri, Alya; Murlina, Nelli; Nurfadly; Hervina (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Pediculosis capitis is one of the parasitic infections that can cause pruritus and allergic reactions. The prevalence of Pediculosis capitis is relatively high and can occur both in developed and developing countries regardless of socioeconomic status. The occurrence of Pediculosis capitis can be caused by poor personal hygiene factors and living environmental conditions, which can also increase the incidence of this ectoparasitic infection. Purpose: To analyze the correlation between personal hygiene and characteristics of the living environment, and the incidence of Pediculosis capitis. Methods: This study is quantitative research with a correlational analysis method and a cross-sectional study approach. Result: The examination of the correlation between poor personal hygiene and the incidence rate of Pediculosis capitis showed a result of 0.000 (p<0.05). Similarly, the examination of the correlation between the characteristics of the living environment and the incidence rate of Pediculosis capitis also showed a figure of 0.000 (p<0.05), indicating that there is a correlation between personal hygiene, and the characteristics of the living environment, and the incidence rate of Pediculosis capitis. Conclusion: There is a significant correlation between personal hygiene, and the characteristics of the living environment, and the incidence of Pediculosis capitis.